THE PERCEIVED IMAGE OF BARCELONA BY SHORT BREAK TOURISTS - Camprubi, Raquel; Prats, Lluis (European Scientific Journal, ESJ, 2013)
During last years research in tourism has put especial attention to tourist image as a factor that influences consumer behaviour. At the same time, previous research confirms that length of stay also is influenced by tourist image. Considering the differences between short break tourists and long stay tourist, and the new city tourism trends; this paper aims to analyse city break tourists considering three variables: tourists’ profile, motivation and perceived image. Barcelona was the destination used as a case study for this explorative research. Findings reveal a classification of three kinds of city break tourists based on socio-economic variables, identifying some substantial differences in their motivations and perceived image of the destination. Although limitations of this study are linked to their explorative character, some future research lines are proposed.